The effect of pre-sowing treatment of seeds with molybdenum and boron on the yield of Zhansaya soybean in the conditions of the Almaty region - Kаbylbekova, G.K.; Didorenko, S.V.; Abugaliyeva, A.I.; Kudaybergenov, M.S.; Аlikulov, Z.A. (Fundamental and Experimental Biology, 2022)
The expansion of the planting acreage and increasing the productivity of such crops as soybeans are a priority trend of the agro-industrial complex of Kazakhstan. In the field of biological safety, there are two ways to solve the problem of increasing the yield: selection-genetic and technological. Using new technologies is the leading approach to develop and provide optimal conditions for the full realization of their genetic potential. Managing the growing season of new varieties of plants through the use of scientifically based crop rotation, as well as using micro-fertilizers and growth stimulants, allows achieving the highest profitability of crop production. Undoubtedly, there is the fact of correlation dependence between the development of cell bacteria and the intensity of photosynthesis. There have been studied the effect of pre-sowing treatment of soybean seeds with solutions of Mo and Co microelements on productivity. All the types of treatment have had a positive effect on productivity. Even the introduction of microelements without inoculationincreased the yield in comparison with the control by 2.3 kg/ha. The biggest deviation from the control was given by the joint treatment of seeds with nitrogen-fixing bacteria and microelements: 8.4 centers/ha. The quality indicators (protein and fat content) were only slightly affected by the types of treatment. When treated only with a nitrogen-fixing drug and its combined use with microelements, the amount of protein in the seeds increased by 0.6 and 0.7 %, respectively, compared with the control.